2009
DOI: 10.1038/jhg.2009.54
|View full text |Cite
|
Sign up to set email alerts
|

The E23K variation in the KCNJ11 gene is associated with type 2 diabetes in Chinese and East Asian population

Abstract: The genes (ABCC8 and KCNJ11) have a key role in glucose-stimulated insulin secretion and thus have always been considered as excellent susceptibility candidates for involvement in type 2 diabetes. Common polymorphisms (KCNJ11 E23K and ABCC8 exon16-3t/c) in these genes have been reported to be associated with type 2 diabetes in various European-descent populations. However, there were inconsistent results in previous studies in East Asian populations and no large case-control studies have been carried out in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 16 publications
5
40
1
Order By: Relevance
“…Despite some reports, which found an association between the E23K polymorphism of Kir6.2 and the development of T2D (Nielsen et al, 2003;Alsmadi et al, 2008;Tabara et al, 2009;Zhou et al, 2009;Abdelhamid et al, 2014), our results showed no association, which was in agreement with other studies (Inoue et al, 1997;Yokoi et al, 2006;Cejková et al, 2007;Cauchi et al, 2008;Keshavarz et al, 2014). The MAF (A-allele) in our study of EuroBrazilians overlaps the 95% confidence interval for several European populations (Table 3), suggesting consistency.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Despite some reports, which found an association between the E23K polymorphism of Kir6.2 and the development of T2D (Nielsen et al, 2003;Alsmadi et al, 2008;Tabara et al, 2009;Zhou et al, 2009;Abdelhamid et al, 2014), our results showed no association, which was in agreement with other studies (Inoue et al, 1997;Yokoi et al, 2006;Cejková et al, 2007;Cauchi et al, 2008;Keshavarz et al, 2014). The MAF (A-allele) in our study of EuroBrazilians overlaps the 95% confidence interval for several European populations (Table 3), suggesting consistency.…”
Section: Discussionsupporting
confidence: 65%
“…E23K is a common polymorphism worldwide and each copy of the susceptibility allele has a modest effect (odds ratio ~1.15) on T2D (Zhou et al, 2009), but due to its high allele frequency, it is likely to have a large effect on population attributable risk (Gloyn et al, 2003). Therefore, the small sample size of our study could be a limitation of the statistical power of the test.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Moreover, more than 50% of type 2 diabetes patients were diagnosed at the age of 45-65 years and have 5-15 years duration of disease. In all, 2041 controls (635 men, 1406 women; age 58.1 ± 9.4 years), 4,20,21 with a FPG concentration o6.1 mmol l À1 , were enrolled from the same geographical area with cases. The overall age and sex distribution of controls were matched with that of case group.…”
Section: Materials and Methods Participantsmentioning
confidence: 99%
“…15,16 To reach sufficient statistical power, another 1152 healthy individuals were selected from a previously studied control set from communities in Pudong District, Shanghai, China. [17][18][19][20][21][22][23] All the samples were enrolled concurrently from 2007 to 2008 and represented as southeastern Han Chinese population; therefore, we combined the two sets of controls in the following statistical analyses. AMD clinical diagnosis was defined strictly in accordance with the International Classification of AgeRelated Maculopathy and Macular Degeneration.…”
Section: Subjectsmentioning
confidence: 99%